An Econometric Analysis of Sea Surface Temperatures, Sea Ice Concentrations and Ocean Surface Current Velocities - Alok Bhargava; Juan A. Echenique (Journal of Marine Science and Engineering, 2022)
This paper analyzed quarterly longitudinal data for 64,800 1 × 1 degree grids during 2000–2019 on sea surface temperatures, sea ice concentrations, and ocean surface current zonal and meridional velocities in the Northern and Southern hemispheres. The methodological framework addressed the processing of remote sensing signals, interdependence between sea surface temperatures and sea ice concentrations, and combining zonal and meridional velocities as the eddy kinetic energy. Dynamic and static random effects models were estimated by maximum likelihood and stepwise methods, respectively, taking into account the unobserved heterogeneity across grids. The main findings were that quarterly sea surface temperatures increased steadily in the Northern hemisphere, whereas cyclical patterns were apparent in Southern hemisphere; sea ice concentrations declined in both hemispheres. Second, sea surface temperatures were estimated with large negative coefficients in the models for sea ice concentrations for the hemispheres; previous sea ice concentrations were negatively associated with sea surface temperatures, indicating feedback loops. Third, sea surface temperatures were positively and significantly associated with eddy kinetic energy in Northern hemisphere. Overall, the results indicated the importance of reducing sea surface temperatures via reductions in greenhouse gas emissions and the dumping of pollutants into oceans for maintaining sea ice concentrations and enhancing global sustainability.